2017
DOI: 10.20538/1682-0363-2017-4-16-29
|View full text |Cite
|
Sign up to set email alerts
|

Free radical oxidation: a pathophysiologist’s view

Abstract: История свободнорадикальной биологии. Счи-тается, что свободнорадикальная биология не име-ет точных исторических корней, но на протяжении нескольких столетий химики ýффективно работали УДК 616-098:577.125.33:577.121.7 DOI: 10.20538/1682616-098:577.125.33:577.121.7 DOI: 10.20538/ -0363-2017 Для цитирования: Колесникова Л.И., Даренская М.А., Колесников С.И. Свободнорадикальное окисление: взгляд патофи-зиолога. Бюллетень сибирской медицины. 2017; 16 (4): 16-29.Свободнорадикальное окисление: взгляд патофизиолога… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 37 publications
1
12
0
2
Order By: Relevance
“…The opposite directivity of biochemical changes during DM1 in different ethnic groups can be mostly related to the genetic factors. The traditional nutritional pattern including the food with enhanced animal fat content can probably promote the adaptive processes and form resistance against the atherosclerotic processes [6]. Our data are corroborated by the clinical presentation of DM1 course with less number of complications in Buryats in comparison with the patients of other ethnic groups and with overall statistical indices.…”
Section: Resultssupporting
confidence: 77%
“…The opposite directivity of biochemical changes during DM1 in different ethnic groups can be mostly related to the genetic factors. The traditional nutritional pattern including the food with enhanced animal fat content can probably promote the adaptive processes and form resistance against the atherosclerotic processes [6]. Our data are corroborated by the clinical presentation of DM1 course with less number of complications in Buryats in comparison with the patients of other ethnic groups and with overall statistical indices.…”
Section: Resultssupporting
confidence: 77%
“…(22)(23)(24) In addition, the development of this disease provoked changes in the fatty acid composition of blood plasma lipids: an increase in the total content of saturated and monounsaturated fatty acids with a reduction in the concentration of polyunsaturated components. (8) The consequence of such destabilization is the development of OS in patients with AH. With respect to the studied problem, it should also be noted that the generation of toxic LPO products is closely related to the synthesis of nitric oxide, the concentration of which positively correlates with the activity of an angiotensin converting enzyme, which is one of the most important factors in the regulation of BP.…”
Section: The Content Of Lpo Products and Components Of Aod System In mentioning
confidence: 99%
“…The limiting factor of the LPO processes in the body is the high activity of antioxidant factors that make up the overall antioxidant status. (8,11) It was found that the increased values of toxic metabolites in hypertensive animals took place against the background of a significant decrease in antioxidant protection factors-TAA and the content of fat-soluble vitamins. It is known that α-tocopherol is a strong antioxidant of exogenous origin.…”
Section: The Content Of Lpo Products and Components Of Aod System In mentioning
confidence: 99%
See 1 more Smart Citation
“…However, under pathological conditions, the uncontrolled production of ROS exceeds the antioxidant capacity of the seminal plasma, resulting in OS. (1,(9)(10)(11)(12) Spermatozoa are particularly vulnerable to OS because they do not have the necessary cytoplasmic antioxidant recovery systems. 20%-40% of infertile men have a higher level of ROS in the semen than in healthy men.…”
Section: Introductionmentioning
confidence: 99%